PENGARUH PENGUATAN NILAI-NILAI DASAR BELA NEGARA TERHADAP PENANGANAN VIRUS CORONA 2019 DI KOTA TERNATE - Taufik Z. Karim (Jurnal Kewidyaiswaraan, 2021)
This research aims to find first, to find out the strengthening of the values ​​of State Defense Basic Training for Prospective Civil Servants, the second role of handling the 2019 corona virus pandemic, and third to find out the effect of strengthening the values ​​of State Defense Basic Training for Candidates for Civil Servants on the handling of the corona virus pandemic 2019. The research method used in this research is quantitative method. The sample used in the study was 40 people for the Basic Training Alumni of Ternate City Civil Servant Candidates. The data collection technique used in the research was literature study and questionnaire distribution. The data analysis technique was carried out by using the simple regression method. The results showed that, first, in general, the learning process for agenda one Basic Training for Civil Servant Candidates for Ternate City has been running well or has succeeded in equipping the participants to form attitudes and behaviors in carrying out their job duties. Second, most of the alumni have taken part or participated in donating energy, thoughts and funds voluntarily in dealing with the 2019 corona virus pandemic. Meanwhile, the third overall value of the effect of Strengthening State Defense Values ​​on Handling the 2019 Corona Virus Pandemic is 43.1%, in other words there are 56.9% influenced by other variables.